ДОСЛІДНИЦЬКІ УМІННЯ ЯК ПОКАЗНИК ГОТОВНОСТІ СТУДЕНТІВ ВИЩОЇ ШКОЛИ ДО ТВОРЧОЇ РОБОТИ (Педагогіка вищої та середньої школи, 2004)
The article deals with the specificity o f investigating skills as an exponent o f future teachers’ readiness to the creative professional activities, their classification is given.